Moving out or staying put? Neighborhood choice, notions of community, and identification(s) of upwardly mobile Turkish-Germans. - Barwick, Christine (My University, 2015)
The work deals with neighborhood choice of upwardly mobile Turkish-Germans, analyzing their motives for staying in a socioeconomically disadvantaged neighborhood, or moving from a disadvantaged to a more advantaged one. Furthermore, the consequences of moving or staying are analyzed, in terms of social capital, network composition, and processes of identification. The focus is twofold. First, the recurring question is for the relevance of place, and specifically the neighborhood as community. Second, particularly when dealing with networks and identification(s), the question is whether there are processes of groupness and social closure, based on ethnic or social class background. For the Turkish-Germans, the neighborhood presents a place which ideally contains a particular set of social relations, emerging through public familiarity and expressed in shared moments of sociability. If these characteristics are present in a neighborhood, irrespective of socioeconomic status, practical and symbolic neighborhood use is high. If a neighborhood, on the other hand, is characterized by anonymity and hostility towards ethnic minorities, neighborhood use is low. In turn, other places with high public familiarity and sociable relations are frequented, which then become important in symbolic terms, for identification.
Keywords: Stadtsoziologie; Wohnen; Bewohner; Wohnstandort; Standortwahl; Mobilität; Nachbarschaft; Segregation; Wanderungsverhalten; Umzug; Wohnungsmarkt; Türke; Deutscher; Ethnizität; Kulturelle Identität; Sozialkapital; Soziales Netzwerk; Sozialer Aufstieg; Status; Image; Benachteiligter Stadtteil